Pre and postnatal effect of maternal environmental tobacco smoke exposure on infant's growth parameters - Nada Ziyad Salim; Ban Sahib Diab (Journal of the Pakistan Medical Association)
Objective: To determine the association between environmental tobacco smoke exposure and growth parameters of infants.